Integration of Physical and Psychological Human Data into Digital Human Modelling for Manufacturing System Design - Johnson, Teegan Laura (Cranfield University, 2021)
Industry 4, the current industrial revolution, is bringing an increase in digitisation to manufacturing. It involves, in part, a move towards using the digital human modelling (DHM) capabilities in computer aided design (CAD) programs to design and monitor products, workstations, and the new technology being introduced into manufacturing working environments. DHM in CAD involves modelling the impact manufacturing products and environments have on those who work in and with them. At present, the focus of CAD programs with integrated DHM tools is the physical impact of manufacturing environments on workers or operators; psychological impacts, however, are missing. This thesis aimed to identify and establish psychological parameters that could improve the capability of DHM for manufacturing system design. Two studies identified psychological equations for integration into DHM CAD, the first established an equation between physical strain and mental workload. This study was preceded by an investigation into the effectiveness of an inertial motion capture suit to identify an effective means of measuring physical strain. The second study investigated the effect of human robot collaboration on perceived trust, workload, and mood, when manipulating robot speed. A predictive equation could only be established for trust; and this equation was integrated into a CAD program, and the reliability was assessed using an experimental mock-up of an Airbus installation process. The equation when integrated into the CAD program was able to successfully predict the trust response of participants in the reliability experiment and, therefore, achieved the aim of this thesis. The implications and limitations of the studies are discussed.
Keywords: Mental Workload; Human Robot Collaboration; Trust; Mood; Quantitative Analysis; Monte Carlo Simulation; Generalised Estimating Equations; Inertial Motion Capture